Bioassay-guided isolation of Fenghuang Dancong tea constituents with α-glucosidase inhibition activities - Zhou, Hua; Liao, Jin; Ou, Juanying; Lin, Jiayu; Zheng, Jie; Li, Yifei; Ou, Shiyi; Liu, Fu (Frontiers in Nutrition, 2022)
An α-glucosidase inhibition assay showed the ethanolic extract of Fenghuang Dancong tea had potential α-glucosidase inhibitory activity. The most bioactive fraction, which was obtained via bioassay-guided isolation of the extract, was further purified to create five compounds, including three novel compounds (1–3). These compounds were analyzed and identified in detail using high-resolution-mass spectrometry and extensive one-dimensional and two-dimensional NMR spectroscopy experiments. Among the compounds, compound 1 contained cis double bonds and showed the strongest α-glucosidase inhibitory activity with an IC50 value of 7.51 μM, which is significantly lower than that of compound 2 with trans double bonds. Enzyme kinetic experiments showed that 1 was a reversible non-competitive α-glucosidase inhibitor.